2018
DOI: 10.1115/1.4041559
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Effectiveness on High-Pressure Turbine Nozzle Guide Vanes Under Realistic Swirling Conditions

Abstract: In modern lean-burn aero-engine combustors, highly swirling flow structures are adopted to control the fuel-air mixing and to provide the correct flame stabilization mechanisms. Aggressive swirl fields and high turbulence intensities are hence expected in the combustor-turbine interface. Moreover, to maximize the engine cycle efficiency, an accurate design of the high-pressure nozzle cooling system must be pursued: in a film-cooled nozzle, the air taken from last compressor stages is ejected through discrete h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The film cooling scheme is made by 8 rows of cylindrical film cooling holes, with four shower head and four pressure side rows. More details on the combustor simulator rig and on NGVs film cooling system can be found in Bacci et al (2018) and Bacci et al (2018b).…”
Section: Test Rigmentioning
confidence: 99%
See 2 more Smart Citations
“…The film cooling scheme is made by 8 rows of cylindrical film cooling holes, with four shower head and four pressure side rows. More details on the combustor simulator rig and on NGVs film cooling system can be found in Bacci et al (2018) and Bacci et al (2018b).…”
Section: Test Rigmentioning
confidence: 99%
“…In addition, a condition without coolant and an in-between condition (M F R = 3.75%) were explored to evaluate the effect of the NGV coolant mass flow rate on the results. A summary of the operating conditions is shown in Table 1, while the row-by-row BR calculation at nominal condition is reported in Bacci et al (2018). It is worth to underline that the exit Mach number of the cascade is relative lower respect to actual engine conditions: even if for instance local sonic conditions could have an impact on the final results, the general conclusions of the paper can be considered valuable to better understand the T u behaviour across cooled NGVs and the impact of cooling flows.…”
Section: Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacci et al [24,25] used a test rig with cooled vanes and combustion chamber to investigate hot streaks and swirling inflow to the vanes. It was found that different aerofoils face significantly different temperature fields.…”
Section: Introductionmentioning
confidence: 99%
“…Cubeda et al [27] compared different numerical methods to the experimental measurements of Bacci et al [25,24], finding that neither RANS of combustion chamber and vanes, nor SAS of the combustion chamber used as a boundary condition to steady RANS gave satisfactory results. RANS simulation gave local adiabatic temperature errors exceeding 150K.…”
Section: Introductionmentioning
confidence: 99%